2014
DOI: 10.1002/ijc.29194
|View full text |Cite
|
Sign up to set email alerts
|

BIRC6 promotes hepatocellular carcinogenesis: Interaction of BIRC6 with p53 facilitating p53 degradation

Abstract: The genes that encode inhibitor of apoptosis proteins (IAPs) are frequently overexpressed in human cancers. However, the expression pattern and clinical significance of BIRC6, a member of IAPs, in hepatocellular carcinoma (HCC) remains unclear. Here we investigated the role of BIRC6 in hepatocellular carcinogenesis. We used immunoblot and immunochemical analyses to determine the levels of BIRC6 in 7 hepatoma cell lines and 160 HCC specimens. We evaluated the proognostic value of BIRC6 expression and its associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 42 publications
(75 reference statements)
0
53
1
Order By: Relevance
“…We predicted several potential target candidates for miR-129-2-3p. Among them, BCL2L2 provoked our interesting due to its oncogenic role in many solid tumors (31)(32)(33). Luciferase report assay confirmed that miR-129-2-3p directly targeted BCL2L2 3'UTR for degradation.…”
Section: Discussionmentioning
confidence: 95%
“…We predicted several potential target candidates for miR-129-2-3p. Among them, BCL2L2 provoked our interesting due to its oncogenic role in many solid tumors (31)(32)(33). Luciferase report assay confirmed that miR-129-2-3p directly targeted BCL2L2 3'UTR for degradation.…”
Section: Discussionmentioning
confidence: 95%
“…The semiquantitative scoring system was based on both the staining intensity (0, negative; 1, weak; 2, intermediate; 3, strong) and the percentage of positive cells (0, 0% positive cells; 1, ≤25% positive cells; 2, 26%–50% positive cells; 3, >50% positive cells). The final score of each sample was obtained by multiplying the scores of staining intensity and percentage of positive cells [25]. We chose five randomized microscopic views of 400-fold magnification of each slide to score and get a composite score.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, cells were incubated with CCK-8 for 1 h. Cell proliferation rate was assessed by measuring the absorbance at 450 nm with the Universal Microplate Reader (BIO-TEK Instruments, Minneapolis, MN, USA). Anchorage-independent growth ability was measured using the colony forming assay and soft agar colony formation assay, as previously [25]. The colonies with diameter >0.1 mm were counted and colony forming efficiency was calculated (Percentage of colonies = Number of colonies formed/Number of cells inoculated × 100%).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, BIRC6 also inhibits apoptosis via negatively regulating p53 protein levels by facilitating its degradation via ubiquitination (Ren et al, 2005;Tang et al, 2014). BIRC6 and treatment resistance.…”
Section: Summary Of the Pleiotropic Functions Of Birc6mentioning
confidence: 99%